Exploring the role of hydraulic conductivity on the contribution of the hyporheic zone to in‐stream nitrogen uptake. Issue 7 (19th August 2019) - Mendoza‐Lera, Clara; Ribot, Miquel; Foulquier, Arnaud; Martí, Eugènia; Bonnineau, Chloé; Breil, Pascal; Datry, Thibault
Abstract: Nitrogen uptake (N‐uptake) within the hyporheic zone provides key ecological services, such as nutrient removal, of stream ecosystems. We hypothesize that the hydraulic conductivity (Kf) of the hyporheic sediments governs nutrient uptake rates through effects on the (a) surface and subsurface flow (i.e., hyporheic flow) and (b) hyporheic N‐uptake. Here, we worked at two hierarchical spatial scales (reach and hyporheic scale) to disentangle the role of Kf on N‐uptake. At the reach scale, we performed coinjected N‐NH4 + and Cl – additions in six reaches with contrasting reach Kf (10 −1 –10 −5 m/s) and simultaneously determined (a) in‐stream N‐uptake (hyporheic+benthic N‐uptake) and (b) hyporheic flow, and (c) N‐uptake and microbial community abundance at the hyporheic scale. Results suggest that Kf determines the contribution of the hyporheic zone to hydrological exchange but that its role varies between scales to determine in‐stream N‐uptake. At the reach scale, Kf variability seems to determine the extent at which the hyporheic zone contributes to hyporheic flow and, thus, to N‐uptake velocity. At the hyporheic scale, Kf seems to indirectly determine hyporheic N‐uptake through the proportion of surface water that enters the hyporheic zone (i.e., relative connectivity) and the abundance of the microbial community. These results suggest an interplay between Kf at both scales and its spatial heterogeneity, which will ultimately drive in‐stream N‐uptake at reach scale. In this sense, we found that Kf can be considered as a unifying variable for stream biogeochemical processes and as an important variable to derive the contribution of hyporheic zone to in‐stream nutrient removal capacity.